FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (2008-2011) - Meri Apriani; Azwir Nasir; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the factors affecting conservatism accounting in manufacturing company listed in BEI (2008-2011). This study use purposive sampling method to choose sample, so there are 26 (twenty six) sample company. The mehod of analysis used in this study is descriptive quantity method, simultaneous regression tes and partial test ( multiple regression analysis using SPSS version 20.0 ). Simultaneous regression test ( F test ) showed that the independent variables studied simultaneously have a significant effect on the accounting conservatism. Partial regression test showed that tax insentive variable has the significant effect to the accounting conservatism. The magnitude of the effect that ( R2 ) by the four the independent variables together against the conservatism 34%, whilw thw remaining 66% is influenced by other variables not examined in this study.Keywords: Accounting Conservatism, Tax Insentive, Managerial Ownership, Debt, Political Cost.